Perlindungan Hukum dalam Sengketa Merek BMW vs BMW Body Man Wear; Studi Putusan Mahkamah Agung Nomor 29.PK/PDT.SUS-HKI/2016 - Risris Bayanillah; Abu Tamrin (JOURNAL of LEGAL RESEARCH, 2019)
Abstract:The main problem in this study is the analysis of the protection of well-known brands, especially in the element of equality that basically applies to non-similar goods. In addition to analyzing the consideration of judges Number 29 PK / Pdt.Sus-HKI / 2016 which contains trademark disputes between BMW brands and BMW Body Man Wear. The research method uses a normative juridical approach. The results showed that the element of equality in principle applies to goods of different types because it is a principal element that exists in the legal order of the brand associated with the distinguishing power element that exists in a brand. The panel of judges in deciding this case considers SEMA Number 3 / BUA.6 / HS / SP / XII / 2015 which states that all cases of filing claims for cancellation of brands that have similarities in principle in non-similar goods, the lawsuit must be declared with amar 'is not acceptable 'because the Government Regulation mandated by Law Number 15 Year 2001 Concerning Trademarks has not yet been enacted.Keywords: Trademark Protection, Elemental Equality Principals, Decision Analysis